Physical Activity, Learning Experience, and Their Influence on Athletic and Sports Performance in the United States: The Mediating Role of Quality of Life - Connor Benjamin; Ali ZaibRasheed (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The purpose of this study is to examine the associations between physical activity (PA), sportsman learning experiences (SLE), and sports performance in a sample of football players from the United States. The study specifically aims to explore the potential moderating effect of physical health impairments (PHYI) and the mediating role of quality of life (QOL) in these relationships. A quantitative cross-sectional methodology was employed to gather data from 300 football players. The data collection process involved the use of self-administered questionnaires, and a convenient sampling technique was utilised. The data that was gathered was subjected to analysis using both demographic and inferential statistics with the assistance of SPSS. The regression analysis demonstrates a statistically significant and positive relationship between physical activity (PA) and both quality of life (QOL) and subjective life expectancy (SLE). Furthermore, the findings suggest that QOL partially mediates the association between PA and SLE. It is worth mentioning that the inclusion of PHYI significantly amplifies the beneficial impact of physical activity on systemic lupus erythematosus (SLE). The aforementioned findings underscore the necessity of implementing all-encompassing athlete development initiatives that prioritise both the physical and mental well-being of individuals, particularly those athletes who are confronted with health-related obstacles. The present study makes a valuable contribution to the ongoing exploration of athlete development and provides practical implications for the design of comprehensive athlete support systems with the goal of improving athletic performance and overall life satisfaction.